Lost highway(s): barriers to postnatal cortical neurogenesis and implications for brain repair - Akhtar, Aslam Abbasi; Breunig, Joshua J. (Frontiers in Cellular Neuroscience, 2015)
The genesis of the cerebral cortex is a highly complex and tightly-orchestrated process of cell division, migration, maturation, and integration. Developmental missteps often have catastrophic consequences on cortical function. Further, the cerebral cortex, in which neurogenesis takes place almost exclusively prenatally, has a very poor capacity for replacement of neurons lost to injury or disease. A multitude of factors underlie this deficit, including the depletion of radial glia, the gliogenic switch which mitigates continued neurogenesis, diminished neuronal migratory streams, and inflammatory processes associated with disease. Despite this, there are glimmers of hope that new approaches may allow for more significant cortical repair. Herein, we review corticogenesis from the context of regeneration and detail the strategies to promote neurogenesis, including interneuron transplants and glial reprogramming. Such strategies circumvent the “lost highways” which are critical for cortical development but are absent in the adult. These new approaches may provide for the possibility of meaningful clinical regeneration of elements of cortical circuitry lost to trauma and disease.